SURGICAL ALGORITHMS FOR DEEP PARAPROCTITIS IN DIABETIC PATIENTS - Kasimov, A.L.; Akhmadjonov, J.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Deep paraproctitis poses a significant challenge in diabetic patients due to atypical presentation, rapid infectious spread, and high postoperative complication rates. Surgical treatment requires not only prompt intervention but also individualized tactics based on anatomical, metabolic, and immunological parameters. This review aims to examine current trends in algorithm-based surgical decision-making for deep perianal infections in the diabetic population. Emphasis is placed on clinical staging, imaging-based classification, glycemic status evaluation, and perioperative optimization. The utility of risk stratification models, minimally invasive drainage techniques, negative pressure wound therapy, and postoperative management strategies is critically reviewed. A framework is proposed for constructing a rational algorithm that incorporates clinical severity, comorbidities, and tissue viability, aiming to improve outcomes and reduce recurrence.